PENGARUH KOMUNIKASI, PENEMPATAN KARYAWAN DAN PEMBINAAN KARIER TERHADAP PRESTASI KERJA KARYAWAN (Studi Pada Bank Pembiayaan Rakyat Syariah (BPRS) Bhakti Sumekar Wilayah Kerja Kabupaten Pamekasan) - jurnalmap map; Akhmad Mukhlis; Chamariyah ÔÇì ÔÇì; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at the Sharia Community Financing Bank (BPRS) Bhakti Sumekar Sumenep. The purpose of this study are: 1) To describe communication, employee placement and employee career development at the Syariah People's Financing Bank (BPRS) Bhakti Sumekar, Pamekasan Regency Working Area. 2) To find out and test the effect of communication, employee placement and career coaching simultaneously on employee work performance at the Sharia Community Financing Bank (BPRS) Bhakti Sumekar Pamekasan Regency Work Area. 3) To find out and test the influence of communication, employee placement and career coaching partially on employee work performance at the Islamic People's Financing Bank (BPRS) Bhakti Sumekar Pamekasan Regency Work Area. Analysis of data using SPSS, this type of research is explanatory research using quantitative research approaches. Keywords: Communication (X1), Placement of employees (X2), Coaching career (X3) and Work achievement (Y).